2011
DOI: 10.1016/j.joep.2010.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Wage inequality and team production: An experimental analysis

Abstract: Numerous survey studies report that human resource managers curb wage inequality with the intent to avoid detrimental effects on workers' morale. However, there exists little controlled empirical evidence demonstrating that horizontal social comparisons and wage inequality have adverse effects on worker behavior. In this paper, we present data from a laboratory experiment that studies the impact of wage inequality on participation and effort choices in team production. Overall, we do not find evidence that wag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…As such, our study is closely related to the widespread debate on the optimal degree of transparency in organizations, in particular with respect to pay secrecy (Charness and Kuhn 2007, Cabrales and Charness 2011, Greiner et al 2011, Nosenzo 2013, Lount and Wilk 2014. Furthermore, our results add an important piece to the picture of the effectiveness of gift exchange in complex, multi-agent employment relations (Maximiano et al 2007, Bartling and von Siemens 2011, Gächter et al 2012, 2013, Gose and Sadrieh 2014. While it seems to be generally possible to establish successful gift-exchange relationships, the necessary prerequisites of perceived fairness, kindness, and trust might turn out as fragile concepts that are apparently susceptible to small and seemingly irrelevant changes in the work environment.…”
Section: Introductionsupporting
confidence: 53%
“…As such, our study is closely related to the widespread debate on the optimal degree of transparency in organizations, in particular with respect to pay secrecy (Charness and Kuhn 2007, Cabrales and Charness 2011, Greiner et al 2011, Nosenzo 2013, Lount and Wilk 2014. Furthermore, our results add an important piece to the picture of the effectiveness of gift exchange in complex, multi-agent employment relations (Maximiano et al 2007, Bartling and von Siemens 2011, Gächter et al 2012, 2013, Gose and Sadrieh 2014. While it seems to be generally possible to establish successful gift-exchange relationships, the necessary prerequisites of perceived fairness, kindness, and trust might turn out as fragile concepts that are apparently susceptible to small and seemingly irrelevant changes in the work environment.…”
Section: Introductionsupporting
confidence: 53%
“…See in particular Fehr and Falk 1999, Charness 1999, Fehr et al 1998, Fehr et al 1993, Fehr and Schmidt, 1999, Charness and Rabin, 2002, and Clark et al, 2010 for lab evidence of relative pay effects. Note however that in experimental effort games, Charness and Kuhn (2007) and Bartling and Von Siemens (2010) find that workers' effort is highly sensitive to their own wages, but unaffected by co-worker wages. Following the theory that ordinal rank matters proposed in psychology by Parducci (1995), some lab studies have shown that rank itself matters (see e.g.…”
Section: A Simple Theoretical Frameworkmentioning
confidence: 91%
“…In Bartling and von Siemens (2011), wages are assigned exogenously with no managers in the experiment, and the authors do not find any effect of wage inequality on effort choices. Nosenzo (2010) compares public versus secret wage treatments and finds effort choices decrease when wages are public (in a threeperson GEG with one manager and two equal-ability workers).…”
Section: Related Literaturementioning
confidence: 95%
“…However, if workers "earn" their productivity by their own doing, then they are more likely to expect merit pay. Similarly, random wage assignments inBartling and von Siemens (2011) do not seem to affect effort in a team production environment.4 Bolton and Werner (2012) report this in 4.9% of the cases andCharness and Kuhn (2007) observe shares of 6.5% and 8.1% in two treatments; neither have manager uncertainty of worker ability. 5 Every organization has its share of incompetent managers, and one of the greatest sources of employee frustration are "idiot" bosses, reports USA Today(Kay, 2013).…”
mentioning
confidence: 94%